The sources of the law of international trade : with special reference to East-West trade - Schmitthoff, Clive M.; International Association of Legal Science; UNESCO (London : Stevens, 1964)
Comprises the report to the London Colloquium of the international association of Legal Science on international trade and the rapid development of legislations and practical customs.
At head of title: International Association of Legal Science.
Reports used as the basis for the colloquium of experts held at King's College, London, from Sept. 24-27, 1962.
Includes bibliographical footnotes and index.
sju 24/01/2019
Loans
Keywords: Commercial law; Conflict of laws; Foreign trade regulation; East-West trade